Molasses-fat blend as an energy source and conditioning agent in feedlot diets - A.S. Flake; Gerry L. Kuhl; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 1998)
Seventy-two yearling crossbred steers were used in an individual feeding trial to evaluate the effects of adding a molasses-fat blend (Synergy® 19/14; Cargill Molasses Liquid Products) to diets at 6 or 12% (dry basis) on growth performance, carcass traits, and feed intake behavior. Dry-rolled corn was processed to a mean geometric particle size of either 2,000 or 3,800 microns. Adding the liquid supplement at 6% to the coarse-rolled finishing ration improved gain (P<.1) and feed efficiency (P<.1). Incorporation of Synergy 19/14 into feedlot rations may help reduce fluctuations in feed intake.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen' s Day; 1998; Beef; Molasses; Fat; Steers; Finishing; Carcasses